2020
DOI: 10.1177/0034355220962215
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Demographic Factors, Transition Services, and Individual Development Account (IDA) Saving Participation Among Transition-Age Youth With Disabilities

Abstract: Saving participation in adolescence is crucial for young adults to achieve financial well-being over their lifetime. Yet, very little is known about the factors that encourage saving participation among youth with disability, including youth who receive supplemental security income (SSI). This study examines relationships between personal and family factors, transition services, and participation in Wisconsin Promoting Readiness of Minors in Supplemental Security Income (PROMISE) individual development account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Recent research has suggested that their social functioning and postschool outcomes may be much more affected by formal skills training than by parents' inputs and expectations (Dekker et al, 2019; Dell'Armo & Tassé, 2019). “Nudges” to invest benefits through employers, financial coaching, and self‐advocacy training may actually prove to be more successful (Jones et al, 2021). Proponents of financial literacy are becoming more and more aware of the importance of employment as a space for financial experiences and education (Fisch et al, 2019; Lotto, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has suggested that their social functioning and postschool outcomes may be much more affected by formal skills training than by parents' inputs and expectations (Dekker et al, 2019; Dell'Armo & Tassé, 2019). “Nudges” to invest benefits through employers, financial coaching, and self‐advocacy training may actually prove to be more successful (Jones et al, 2021). Proponents of financial literacy are becoming more and more aware of the importance of employment as a space for financial experiences and education (Fisch et al, 2019; Lotto, 2020).…”
Section: Discussionmentioning
confidence: 99%